Climate change governance - Meadowcroft, James (Policy research working paper, 2009)
"Climate change governance poses difficult challenges for contemporary political/administrative systems. These systems evolved to handle other sorts of problems and must now be adapted to handle emerging issues of climate change mitigation and adaptation. This paper examines long-term climate governance, particularly in relation to overcoming "institutional inertia" that hampers the development of an effective and timely response. It argues that when the influence of groups that fear adverse consequences of mitigation policies is combined with scientific uncertainty, the complexity of reaching global agreements, and long time frames, the natural tendency is for governments to delay action, to seek to avoid antagonizing influential groups, and to adopt less ambitious climate programs. Conflicts of power and interest are inevitable in relation to climate change policy. To address climate change means altering the way things are being done today - especially in terms of production and consumption practices in key sectors such as energy, agriculture, and transportation. But some of the most powerful groups in society have done well from existing arrangements, and they are cautious about disturbing the status quo. Climate change governance requires governments to take an active role in bringing about shifts in interest perceptions so that stable societal majorities in favor of deploying an active mitigation and adaptation policy regime can be maintained. Measures to help effect such change include: building coalitions for change, buying off opponents, establishing new centers of economic power, creating new institutional actors, adjusting legal rights and responsibilities, and changing ideas and accepted norms and expectations. "--World Bank web site